2019
DOI: 10.1088/1367-2630/ab3acf
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced anomalous Hall effect in massless Dirac fermion systems and topological insulators with dissipation

Abstract: Employing the quantum Liouville equation with phenomenological dissipation, we investigate the transport properties of massless and massive Dirac fermion systems that mimics graphene and topological insulators, respectively. The massless Dirac fermion system does not show an intrinsic Hall effect, but it shows a Hall current under the presence of circularly-polarized laser fields as a nature of a optically-driven nonequilibrium state. Based on the microscopic analysis, we find that the lightinduced Hall effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 54 publications
(93 reference statements)
3
51
0
Order By: Relevance
“…Therefore, in experiments a delicate balance needs to be struck between the time necessary to establish the Floquet phase and the maximum time the material can sustain the radiation. In this context it is important to note that dissipative systems, where the energy can redistributed to a heat bath, can help to stabilize the Floquet phase [13,76,79]. In the next section, instead, we will explore the possibility to achieve establishing Floquet dressed states without the continued transfer of energy into the system.…”
Section: Experimental Observation Of Floquet Topological Phasesmentioning
confidence: 99%
“…Therefore, in experiments a delicate balance needs to be struck between the time necessary to establish the Floquet phase and the maximum time the material can sustain the radiation. In this context it is important to note that dissipative systems, where the energy can redistributed to a heat bath, can help to stabilize the Floquet phase [13,76,79]. In the next section, instead, we will explore the possibility to achieve establishing Floquet dressed states without the continued transfer of energy into the system.…”
Section: Experimental Observation Of Floquet Topological Phasesmentioning
confidence: 99%
“…This opens up the realistic prospect of a finite-field topological transition in solid-state experiments. A future task is to study theoretically the ultrafast light-induced transport properties of TBG for realistic driving pulses especially in the mid-infrared and for smaller twisting angles near 1.7 • , including the effects of excitation and dissipation in real time, which is a much more formidable task for TBG compared to a single branch of Dirac fermions [32,33]. In particular, real-time signatures of tunneling into topological edge states might provide additional insights [70].…”
Section: Discussionmentioning
confidence: 99%
“…In solids, key progress has been made for instance in observing Floquet-Bloch states in time-resolved photoemission spectroscopy [30] or with the recently demonstrated light-induced anomalous Hall effect in graphene under circularly polarized laser driving [31][32][33]. However, the concept of Floquet engineering of a material's topological properties [34][35][36][37][38][39][40][41][42][43] has been limited to very few material systems so far.…”
Section: Introductionmentioning
confidence: 99%
“…In the high-frequency regime, the laser drive is not in resonance with transitions and the heating can take exponentially long times to set in [33,93]. When the drive frequency is in resonance, one needs to take into account relaxation processes to fully describe the system, such as coupling with phonons which can act as a reservoir [94][95][96]. Interestingly, a recent study on dissipative Floquet systems has shown that for resonant and strong-enough drives, Floquet states can develop if the decoherence time is shorter than the period of the drive [97].…”
Section: B Intermediate Frequencymentioning
confidence: 99%